The role of Fc receptors in HIV prevention and therapy. Issue 1 (November 2015) - Boesch, Austin W.; Brown, Eric P.; Ackerman, Margaret E.
Abstract: Over the past decade, a wealth of experimental evidence has accumulated supporting the importance of Fc receptor (FcR) ligation in antibody‐mediated pathology and protection in many disease states. Here we present the diverse evidence base that has accumulated as to the importance of antibody effector functions in the setting of HIV prevention and therapy, including clinical correlates, genetic associations, viral evasion strategies, and a rapidly growing number of compelling animal model experiments. Collectively, this work identifies antibody interactions with FcR as important to both therapeutic and prophylactic strategies involving both passive and active immunity. These findings mirror those in other fields as investigators continue to work toward identifying the right antibodies and the right effectors to be present at the right sites at the right time.